Pengaruh Return on Asset, Debt to Equity Ratio, Earnings per Share terhadap Harga Saham Perbankan - Putri, Firdianti Permata; Susilowati, Endah (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to examine the effect of financial performance proxied by Return on Assets (ROA), Debt to Equity Ratio (DER), and Earnings per Share (EPS) on stock prices of banking companies included in the IDX80 index for the 2020–2024 period. This research employs a quantitative approach using multiple linear regression analysis. The sample consists of seven banking companies selected through purposive sampling, resulting in 35 observations. Secondary data were obtained from annual financial statements and stock price data published by the Indonesia Stock Exchange and analyzed using SPSS version 25. The results indicate that ROA and DER do not have a significant effect on stock prices, while EPS has a significant negative effect. Simultaneously, ROA, DER, and EPS do not significantly affect stock prices. The coefficient of determination shows that the model explains a relatively small portion of stock price variation, suggesting that other factors outside the model influence IDX80 banking stock price.